Phenomenology of Organizational Silence (Case Study Farhangian University) - Iraj Mehdizadeh; Saeed Rajaipour; Seyed Ali Siadat (مدیریت دولتی)
Objective Organizational silence is a prevalent issue in contemporary organizations, and neglecting it can have negative consequences on individual, group, and organizational levels. This research aims to explore the lived experiences of faculty members and staff to identify the factors contributing to organizational silence at Iranian Farhangian University. Methods This research adopted a qualitative approach with a phenomenological method. The participants were faculty members at Farhangian University in the 9th region of eastern Iran. To identify the factors influencing organizational silence, a purposive sampling method with maximum variation was used, taking into account participants' educational backgrounds, personal experiences, and perceptions of organizational silence. The number of participants reached theoretical saturation with 16 individuals. The research instrument was a semi-structured interview. To ensure the reliability of the interviews, the Guba and Lincoln criteria (credibility, transferability, dependability, and confirmability) were applied. The inter-coder reliability was 86%, and confirmability was achieved through peer review. Data analysis was conducted using Smith's 6-step content analysis and coding process with Max.Q.DA software. Results The interview analysis results were organized into three main categories: external organizational, internal organizational, and individual, with 11 main themes and 64 subthemes. In the external organizational category, the main themes are political and social factors. In the internal organizational category, the main themes include structural, communicative, managerial, human resources, supervisory, economic factors, and organizational climate. In the individual category, the main themes are knowledge and motivation. Upon further review, it was determined that the structural theme consists of organizational breadth, decision-making centralization, hierarchical structure, disregard for organizational values, and cumbersome rules and regulations. The communication theme includes external organizational interactions, one-way communication flow, visibility of a specific group, prevalence of informal relationships, use of social media within the university, and negative reactions to colleagues' comments. Several management issues were identified, including a lack of critical thinking among managers, failure to implement ideas, managers ignoring reality, lack of transparency in decision-making, authoritarian management, and intolerance for negative feedback. Gender discrimination in the delegation of authority, lack of promotion based on merit, lack of recruitment and employment based on openness and creativity, absence of a meritocracy, lack of appreciation for employees' efforts, and job insecurity were grouped under the human resources theme. The supervision and control theme revealed that securitization of the work environment, emphasis on employee control, university control processes, external regulatory bodies, and the silent punishment and marginalization of employees are significant factors. In the economic theme, the focus was on rewarding practical proposals, the prevailing economic conditions of individuals, and urgent economic needs such as salary increases and job security. Concerns about freedom of speech, compliance and obedience, poor quality of the work environment, lack of a supportive atmosphere, prevalence of a culture of indifference, and flattery and praise were raised in discussions of the organizational climate theme. In the individual category, the knowledge and motivation themes were explored. The knowledge theme encompasses several key issues: organizational knowledge insufficiency, low experience among administrative staff, attention to rumors instead of official information channels, lived experiences of the consequences of participation, and the inability to articulate issues. The motivation theme includes individual expectations, personal goals, perceived inability to effect change, psychological safety, work motivation, distrust, resilience, reduced self-confidence, learned helplessness, lack of belonging, suppression of voice, job insecurity, inability to voice concerns, work overload, and individual considerations such as expediency, position-taking, and vested interests. Conclusion Based on the research findings, the following recommendations can be made to reduce and prevent organizational silence at Farhangian University as a negative organizational behavior: